Environmental Regulation of the Distribution and Ecology of Bdellovibrio and Like Organisms - Williams, Henry N.; Chen, Huan (Frontiers in Microbiology, 2020)
The impact of key environmental factors, salinity, prey, and temperature, on the survival and ecology of Bdellovibrio and like bacteria (BALO) including the freshwater/soil non-halotolerant group and the halophilic Halobacteriovorax strains has been assessed based on a review of the data in the literature addressing these areas. These topics have been studied by numerous investigators for six decades now, and much valuable information has been amassed and reported. The collective data shows that salinity, prey, and temperature play a major role in not only the growth and survival of BALO but also the structure and composition of BALO communities and the distribution of the predators. Salinity is a major determinant in the selection of BALO habitats, distribution, prey bacteria, and systematics. Halophilic BALOs require salt for cellular functions and are found only in saltwater habitats and prey primarily on saltwater bacteria. On the contrary, freshwater/terrestrial BALOs are non-halotolerant and inhibited by salt concentrations above 0.5%, and are restricted to freshwater, soils, and other low salt environments. They prey preferentially on bacteria in the same habitats. The halophilic BALOs are further separated on the basis of their tolerance to various salt concentrations. Some strains are found in low salt environments and others in high salt regions. In situ studies have demonstrated that salinity gradients in estuarine systems govern the type of BALO communities that will persist within a specific gradient. Bacterial prey for BALOs functions more than just being a substrate for the predators, and include the potential for different prey species to structure the BALO community at the phylotype level. The pattern of susceptibility or resistance of various bacteria species has been used almost universally to differentiate strains of new BALO isolates. However, the method suffers from a lack of uniformity among different laboratories. Differences in temperature growth range among different BALO groups and strains has been demonstrated in many laboratory experiments. The temperature optima and growth range for the saltwater BALOs is typically lower than that of the freshwater/terrestrial BALOs. The collective data shows that environmental factors have a great impact on BALO ecology.